Experimental Study on the Impact of External Geometrical Shape on Free and Forced Convection Time Dependent Average Heat Transfer Coefficient during Cooling Process - Abd, Sundus Hussein (Al-Khwarizmi Engineering Journal, 2012)
In this research, an experimental study was conducted to high light the impact of the exterior shape of a cylindrical body on the forced and free convection heat transfer coefficients when the body is hold in the entrance of an air duct. The impact of changing the body location within the air duct and the air speed are also demonstrated. The cylinders were manufactured with circular, triangular and square sections of copper for its high thermal conductivity with appropriate dimensions, while maintaining the surface area of all shapes to be the same. Each cylinder was heated to a certain temperature and put inside the duct at certain locations. The temperature of the cylinder was then monitored. The heat transfer coefficient were then calculated for forced convection for several Reynolds number (4555-18222).The study covered free convection impact for values ​​of Rayleigh number ranging between (1069-3321). Imperical relationships were obtained for all cases of forced and free convection and compared with equations of circular cylindrical shapes found in literature. These imperical equations were found to be in good comparison with that of other sources.